The Effect of the PBL-STEM on Students’ Critical Thinking Skills - Awaludin, Robi; Aripin, Aripin; Makiyah, Yanti Sofi (Department of Physics Education, Universitas Mataram, 2025)
The low level of students' critical thinking skills is one of the main challenges in education, often caused by a lack of variety in instructional models. To address this issue, the researcher implemented the Problem-Based Learning model integrated with Science, Technology, Engineering, and Mathematics (PBL-STEM). This study aims to examine the effect of the PBL-STEM model on students' critical thinking skills. The research employed a nonequivalent control group design, involving two groups of students: an experimental group taught using the PBL-STEM model and a control group taught using the conventional PBL model. The subjects were Grade 10 science students (X MIPA) at a senior high school. Data were collected through a critical thinking skills test consisting of 10 validated essay questions, with a reliability coefficient of 0.649. The results indicate that the application of the PBL-STEM model effectively enhances students’ critical thinking skills, with an N-Gain score of 72%, categorized as high. The most significant improvement was observed in the indicators of elementary clarification (the ability to understand and clarify basic concepts) and inference (the ability to draw logical conclusions). A significance test revealed a statistically significant difference between the experimental and control groups, confirming that the PBL-STEM model has a substantial impact on developing students' critical thinking skills.. These findings suggest that the PBL-STEM model not only strengthens students’ analytical and logical reasoning but also provides a learning experience that is relevant to real-world contexts. The study recommends the implementation of the PBL-STEM model as an innovative teaching method to foster critical thinking skills, particularly within science and technology-based learning environments.